Re-orienting the fundamentals human rights and new connections in EU-Asia relations - Wiessala, Georg (Ashgate Pub., 2006)
This volume offers an investigation of the ways in which matters of human rights give shape to the European Union's interaction with Asia. The book seeks to propose a more inclusive, holistic, understanding of the significance and potential of the human rights discourse in East-West contacts. It is aimed at a wide readership from the disciplines of Politics, International Relations, Asian Studies, Law and Human Rights.